2021
DOI: 10.3390/electronics10141711
|View full text |Cite
|
Sign up to set email alerts
|

A Real-Time Detection Algorithm for Kiwifruit Defects Based on YOLOv5

Abstract: Defect detection is the most important step in the postpartum reprocessing of kiwifruit. However, there are some small defects difficult to detect. The accuracy and speed of existing detection algorithms are difficult to meet the requirements of real-time detection. For solving these problems, we developed a defect detection model based on YOLOv5, which is able to detect defects accurately and at a fast speed. The main contributions of this research are as follows: (1) a small object detection layer is added t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(121 citation statements)
references
References 13 publications
2
119
0
Order By: Relevance
“…We evaluated the performance of the recognition models based on the mAP value. The higher the value, the better the average detection accuracy [40]. Tables 3 and 4 compare the mAP values and inference times of four different YOLOv5 models with pre-trained weights, respectively.…”
Section: Comparison and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the performance of the recognition models based on the mAP value. The higher the value, the better the average detection accuracy [40]. Tables 3 and 4 compare the mAP values and inference times of four different YOLOv5 models with pre-trained weights, respectively.…”
Section: Comparison and Resultsmentioning
confidence: 99%
“…Bochkovskiy et al [25] proposed YOLOv4, consisting of CSPDarknet53 as a backbone network and spatial pyra-mid pooling (SPP), with PANet as the neck part and YOLOv3 as the head part. YOLOv5 is the latest YOLO version that uses the CBL (Conv2D + Batch Normal + LeakyRELU) module as the basic convolution module and the BottleneckCSP module for feature extraction [39,40]. YOLOv5 includes different models, such as YOLOv5s, YOLOv5m, YOLOv5l, and YOLOv5x, which differ by the width and depth of the BottleneckCSP module [41].…”
Section: Yolo Algorithmmentioning
confidence: 99%
“…At the same time, it has inherited the YOLO series, which is easy to deploy, and has made some empirical improvements to construct a new high-performance detector. When choosing the benchmark model of YOLOX, the authors believes that the Yolov4 [ 16 ] and Yolov5 [ 17 ] series may have some over-optimization from the perspective of the algorithm based on the anchor frame; hence, they finally chose Yolov3 [ 18 ] and combined it with the SPP [ 19 ] components to develop the Yolov3_spp version with better performance. Based on this, the authors proposed the network structure of YOLOX-Darknet53, as shown in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Presently, the majority of researchers focus on improving the static detection effect of different fruit targets [20][21][22]. However, related studies on the dynamic tracking and accurate counting of green citrus have seen less attention.…”
Section: Introductionmentioning
confidence: 99%